ANTIUROLITHIATIC ACTIVITY OF NATURAL CONSTITUENTS ISOLATED FROM AERVA LANATA FLOWERS (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A well-known traditional herb Aerva lanata, broadly used in India for treatment of different ailments such as urolithiasis. Pashanabheda is used as antiurolithiatic in Ayurveda. In the present study, flowers of A. lanata were selected for isolation of active constituents and screening for in vitro antiurolithiatic potentials, as literature supports that flowers have the highest quantity of natural components when compared with the other parts. Hydroalcoholic (80%-water, 20%-alcohol) extract of A. lanata flowers was prepared and fractionation with different organic solvents.. The two fractions (ethyl acetate and n-butanol) were subjected to isolation of active constituents using column chromatography technique, followed by purification of the isolated constituents by preparative high performance thin layer chromatography (HPTLC)and then the individual components were characterized by IR spectrophotometery. Finally, in vitro antiurolithiatic activity was screened by nucleation and aggregation assay. In the aggregation assay, gradual decrease in the calcium oxalate (CaOx) crystal nucleation as well as growth was observed by light microscopy. The findings of the nucleation assay indicate that phytoconstituents inhibited the crystallization of CaOx in solution. The size and the number of calcium oxalate crystals decreased with increasing concentration of the phytoconstituents. The increasing concentrations of Quercetin and betulin (100, 200, 300, 400 and 500 μg/mL) inhibited the CaOx crystal growth. The isolated quercetin and betulin from A. lanata have shown antiurolithiatic effect by significantly reducing the CaOx crystal growth.